X(index)1 + X(index)2 = 0 X(index)2 + X(index)3 =-8 X(index)1 + X(index)3 =4
asked Nov 17, 2014 in Algebra 2 Answers by anonymous

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

From the 1st eqn X2=-X1, and we can substitute this value for X2 in eqn 2: -X1+X3=-8.
Add this to eqn 3: 2X3=-4, so X3=-2.
Using eqn 3 again we have X1-2=4, so X1=6 and therefore X2=-6.
Test all these values in the three eqns to prove that all are satisfied.
answered Nov 28, 2014 by Rod Top Rated User (416,580 points)
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
77,829 questions
81,437 answers
1,761 comments
60,404 users